Mixed-Resolution High-Q Sensor Based on Hybridized Spoof Localized Surface Plasmons - Wang, Jiangpeng; Zhang, Jingjing; Gao, Hao; Fu, Xiaojian; Bao, Di; Cui, Tie Jun (Frontiers in Physics, 2022)
Spoof localized surface plasmons (LSPs) have proven significant advantages in sensing and detection. In this work, we propose a high-Q-factor and high-sensitivity hybridized spoof LSP sensor and a mixed-resolution algorithm. The sensor consists of two concentric inner and outer LSP structures with corrugated rings coupled to each other. The ahcieved Q factor is up to 178, and the sensing figure of merit (FoM) is up to 30. Moreover, a mixed-resolution algorithm, combined with multiple resonant peaks, is proposed to enhance the Q factor and sensing FoM. This algorithm doubles the Q factor and sensing FoM effectively. This mixed-resolution sensor has a wide range of application prospects in the field of high-frequency on-chip resonators and sensors.